The acting of the Academic League of Clinical and Surgical Anatomy in the pandemic: an experience report (Research, Society and Development, 2022)
Due to the Covid-19 Pandemic, in Brazil, the face-to-face activities of medical courses and academic leagues were suspended, both faced difficulties to readjust their activities to the remote/virtual format. This article aims to report the experience of the Clinical and Surgical Anatomy League at the Federal University of Paraná, Toledo Campus, with an emphasis on adapting face-to-face activities to the remote/virtual teaching environment and on contributions to the learning of anatomy in the pandemic. This is a descriptive, cross-sectional, retrospective, qualitative study, an experience report. During the pandemic, numerous activities were carried out on online platforms, biweekly classes, mostly open to the public and certified, posts of revisional materials on the league's Instagram, such as “AnatoCards” and dissemination of classes/events. The First Conference on Clinical and Surgical Anatomy of the West of Paraná was held online, with speakers from different medical specialties and regions of the country, reaching more than 2500 people. Creation of “Anatodúvidas”, in 2021, on Instagram, an extension project of the league, which democratized access to anatomical knowledge, scientifically based, in accessible language, to the community. A story was published in Journal Local to increase the league's visibility to thousands of people. The research incentive resulted in two publications of abstracts in the Congress of Medicine. Therefore, the league’s role in the pandemic contributed to the support of the teaching, research and extension pillars, and stimulated the engagement of students. This resulted in a wide promotion, extension, and improvement of anatomical knowledge, contributing to a more humane and complete medical education, broadly benefiting the community.